Acceptance and Perception of Teachers and Students Regarding the Appropriateness of Using AI Chatbots in the Classroom - Abiodun, T. O Abiodun, T. O; Chinaka, T.W Chinaka, T.W; Asanre, A. A Asanre, A. A; Siphokazi, V Siphokazi, V (Journal of Educational Sciences, 2026)
This study examined the acceptance and perception of teachers and learners regarding the appropriateness of using AI chatbots in the classroom. Using a descriptive survey research approach, the study was carried out. The sample for the study consisted of 384 randomly chosen respondents, 24 teachers, and 360 students in six (6) secondary schools from three (3) local government in Ogun State, Nigeria. This study used simple random sampling as its sampling technique. Data was gathered using a structured questionnaire called "Acceptance and Perceptions of Teachers and Students Regarding the Use of AI." Three research questions were addressed and two hypotheses were investigated. Using both descriptive and inferential statistics (e.g., mean and SD) and inferential statistics (e.g., independent t-test at p<0.05), it was revealed by the findings that the acceptance of the usage of AI in classroom by the teachers and students differs significantly, and also, the study found that teachers and students perception on the use of AI in teaching and learning is differs significantly, and that the use of AI chatbots in teaching and learning is crucial. Among other things, the government should create legal norms and regulations governing the use of AI chatbots by instructors and students.